The expected devaluation in Peru: 1975-1985 - Li Carrillo, José Espósito (1988)
The expectation about the future value of the exchange rate play a crucial role in the peruvian economy. However, this variable has not been studied by both peruvian economic researchers and policy markers. Because of this the present paper inteds to develop a framework of analysis in order to measure exchange rate expectations. This puorpose is acomplished by using statistical bayesian methods.